Okazionalizmi u hrvatskome jeziku na internetu - Štebih Golub, Barbara (Slavia Centralis, 2020)
CROATIAN OCCASIONALISMS ON THE INTERNET The topic of this article are nonce words or occasionalisms in Croatian language of the web. This analysis is based on the corpus collected during 2015 and 2016 from the web editions of the daily newspapers, portals, web forums and reader’s comments of articles. The focus is on word formation processes used in creation of occasionalisms: derivation, compounding, blending, eponymisation, graphoderivation, and non-systematic formation. The role of analogy and context in comprehension of occasionalisms is also discussed.